Mekanisme dan Implikasi Hukum Pengalihan Hutang Piutang dalam Perspektif KUHPerdata dan Hukum Islam - Muhammad Ridha (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2023)
This study aims to analyze the mechanism of debt transfer in the Civil Code, specifically regulated in Articles 1820 to 1825, which govern the transfer of debt responsibility from the old debtor to a new debtor with the creditor's consent. This study also examines the role of the guarantor in ensuring the fulfillment of the new debtor's obligations in the event of default. Additionally, this research compares the concept of debt transfer in Islamic law, known as hawalah, which is regulated in the Qur'an, Hadith, the DSN-MUI Fatwa, and the Islamic Banking Law. The study explores how hawalah offers flexibility in managing debts while adhering to the principles of justice, transparency, and public welfare in accordance with maqashid sharia. The methods used in this research include a descriptive approach to describe existing legal facts, a comparative study between Islamic law and civil law, and library research to gather data from various sources. The findings show that the transfer of debt in the Civil Code includes clear provisions regarding the rights and obligations of the parties involved, including the guarantor mechanism. In Islamic law, hawalah provides a flexible solution for debt transfer with more just and transparent principles. The study also finds that while the debt transfer mechanism has benefits, there are legal challenges and conflicts of interest that may hinder its effectiveness, requiring clear agreements and consent from all parties to prevent disputes.